Decision‐making around admission to intensive care in the UK pre‐COVID‐19: a multicentre ethnographic study. (3rd November 2020) - Griffiths, F.; Svantesson, M.; Bassford, C.; Dale, J.; Blake, C.; McCreedy, A.; Slowther, A‐M.
Summary: Predicting who will benefit from admission to an intensive care unit is not straightforward and admission processes vary. Our aim was to understand how decisions to admit or not are made. We observed 55 decision‐making events in six NHS hospitals. We interviewed 30 referring and 43 intensive care doctors about these events. We describe the nature and context of the decision‐making and analysed how doctors make intensive care admission decisions. Such decisions are complex with intrinsic uncertainty, often urgent and made with incomplete information. While doctors aspire to make patient‐centred decisions, key challenges include: being overworked with lack of time; limited support from senior staff; and a lack of adequate staffing in other parts of the hospital that may be compromising patient safety. To reduce decision complexity, heuristic rules based on experience are often used to help think through the problem; for example, the patient's functional status or clinical gestalt. The intensive care doctors actively managed relationships with referring doctors; acted as the hospital generalist for acutely ill patients; and brought calm to crisis situations. However, they frequently failed to elicit values and preferences from patients or family members. They were rarely explicit in balancing burdens and benefits of intensive care for patients, so consistency and equity cannot be judged. The use of a framework for intensive care admission decisions that reminds doctors to seek patient or family views and encourages explicit balancing of burdens and benefits could improve decision‐making. However, a supportive, adequately resourced context is also needed.